On the Forecast Horizon of Magnetospheric Dynamics: A Scale‐to‐Scale Approach. Issue 11 (8th November 2018) - Consolini, Giuseppe; Alberti, Tommaso; De Michelis, Paola
Abstract: The Earth's magnetosphere is characterized by a complex dynamics resulting from the interaction of different multiscale processes which can be both directly driven/triggered by the interplanetary magnetic field and the solar wind, and due to internal processes of the magnetosphere. Recently, Alberti et al. (2017, https://doi.org/10.1002/2016JA023175 ) have shown that the fluctuations at distinct timescales of some geomagnetic indices differently respond to interplanetary changes during geomagnetic storms. In detail, using an information theory based approach it has been shown that geomagnetic indices fluctuations occurring at long timescales (typically longer than 200 min) are correlated with physical quantities characterizing the changes of the interplanetary conditions, while the short timescale ones (typically shorter than 200 min) do not seem to be directly related to the same physical quantities. The aim of this work is to identify the nature and character of the scale‐to‐scale fluctuations of two geomagnetic indices, AE and SYM‐H, capable of monitoring different geomagnetic current systems related to the occurrence of geomagnetic storms and substorms. By applying the theory of dynamical systems, we investigate the scale‐to‐scale correlation dimension D 2 and the Kolmogorov entropy K 2 showing the occurrence of a topological phase transition phenomenon between long and short‐timescale fluctuations. Furthermore, our results clearly show that the forecast horizon of fluctuations occurring at timescales shorter than 200 min dramatically decreases down to ∼2 min. The consequences of this result in the framework of Space Weather forecasting is briefly outlined and discussed. Key Points: A dynamical system approach is used to describe magnetospheric dynamics as seen by scale‐to‐scale fluctuations of SYM‐H and AE indices Correlation dimension D 2 and Kolmogorov entropy K 2 are scale‐dependent but independent on the phases of the solar activity cycle Forecast horizon is very small (approx. 2 min) for short‐timescale fluctuations, which are crucial for Space Weather purposes